2011
DOI: 10.1016/j.micpath.2011.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Tn5AraOut mutagenesis for the identification of Yersinia pestis genes involved in resistance towards cationic antimicrobial peptides

Abstract: Bacterial pathogens display a variety of protection mechanisms against the inhibitory and lethal effects of host cationic antimicrobial peptides (CAMPs). To identify Yersinia pestis genes involved in CAMP-resistance, libraries of DSY101 (KIM6 caf1 pla psa) minitransposon Tn5AraOut mutants were selected at 37°C for resistance to the model CAMPs polymyxin B or protamine. This approach targeted genes that needed to be repressed (null mutations) or induced (upstream PBAD insertions) for the detection of CAMP resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 77 publications
2
25
0
1
Order By: Relevance
“…In that study, an feoC mutant had increased resistance to certain antimicrobial peptides. Similar results were obtained by overexpressing feoAB, leading the authors to conclude that FeoC was repressing expression of the feo operon (38). In our hands, the expression of the feoB::lacZ reporter was unaffected by a mutation in feoC (Fig.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In that study, an feoC mutant had increased resistance to certain antimicrobial peptides. Similar results were obtained by overexpressing feoAB, leading the authors to conclude that FeoC was repressing expression of the feo operon (38). In our hands, the expression of the feoB::lacZ reporter was unaffected by a mutation in feoC (Fig.…”
Section: Resultssupporting
confidence: 85%
“…Based on these data, and the predicted LysR-like winged-helix N-terminal motif (12), Guo et al proposed that the Y. pestis FeoC is a regulator of feoAB that represses expression in vitro (38). However, our studies using transcriptional reporters failed to show any regulatory effects on transcription from the feo promoter in vitro due to an feoC mutation (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Similar results were reported recently by Guo et al, who showed that the induced expression of the pgbP (also known as pmr) operon in Y. pestis conferred resistance to polymyxin B but not to human cathelicidin LL-37 (23). The reason for this phenotype is unclear, but it appears that the effects of changes in LOS and/or bacterial surface characteristics on Y. pestis sensitivity to antimicrobial peptides are different for cyclic (polymyxin B) versus ␣-helical (cathelicidin) peptides.…”
Section: Discussionsupporting
confidence: 89%